Analysis of Factors Influencing Learning Difficulties in History in Grade X Students at Nurul Amaliyah Private Senior High School Tanjung Morawa - Maibang, Listia; Putri, Nadira Aulia; Ryanto, Ammar Zhafran (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This study aims to identify the factors that cause the learning difficulties of history class X students at SMA Swasta Nurul Amaliyah Tanjung Morawa, which is motivated by the low interest and achievement of student learning, coupled with the students' assumption that history is a boring subject. The method used is descriptive qualitative with data collection techniques in the form of observation, interviews, and documentation. The results revealed that the obstacles in learning history consist of internal and external factors. Internal factors include lack of motivation to learn, negative views of history subjects, low academic achievement, lack of confidence, and inconsistent learning patterns. Meanwhile, external factors include influences from the family and peer environment, the limited ability of teachers to manage learning, teaching methods that are less varied, limited learning media, and lack of available learning resources. Based on these findings, innovations are needed in the history learning process, such as the utilization of interactive learning media, contextual approaches, and increased active student participation to create more interesting and effective learning.